THE ROLE OF ISLAMIC RELIGIOUS COUNSELORS IN MINIMIZING DIVORCE CASES IN LARANGAN DISTRICT, BREBES REGENCY - Nurkhojin; Rohidin (PT. Cadas Insan Madani, 2026)
This study examines the role of Islamic Religious Extension Workers in minimizing divorce cases in Larangan District, Brebes Regency, Indonesia. The increasing number of divorce cases in Indonesian society has become a social and religious concern that requires preventive efforts involving various stakeholders, including Islamic Religious Extension Workers under the Ministry of Religious Affairs. This research aims to analyze the strategies, functions, and effectiveness of Islamic Religious Extension Workers in providing premarital guidance, family counseling, religious education, and mediation for married couples experiencing domestic conflicts. The study employed a qualitative approach with a field research design. Data were collected through observations, in-depth interviews with Islamic Religious Extension Workers, community leaders, and married couples, as well as documentation studies. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that Islamic Religious Extension Workers play significant roles as educators, counselors, mediators, and motivators in strengthening family resilience and preventing divorce. Their activities include premarital counseling programs, religious lectures on family harmony, individual counseling sessions, and mediation efforts for couples facing marital disputes. However, several challenges were identified, including limited human resources, low public awareness of counseling services, and socio-economic factors contributing to marital conflicts. The study concludes that strengthening the capacity and outreach of Islamic Religious Extension Workers is essential to reducing divorce rates and promoting harmonious families within the community.